Women who don?t wait in line break the mold, lead the way - Saujani, Reshma (Michigan Brilliance Audio, 2013)
" There?s never been a better time to be a woman. We live in an era when girls are told they can do anything. So why aren?t we seeing more women rising to the top ranks of corporations and the government? Why don?t our girls have more women in leadership roles to look up to? Women Who Don?t Wait In Line is an urgent wake-up call from politico and activist Reshma Saujani. The former New York City Deputy Public Advocate and founder of the national nonprofit Girls Who Code argues that aversion to risk and failure is the final hurdle holding women back in the workplace. Saujani advocates a new model of female leadership based on sponsorship--where women encourage each other to compete, take risks, embrace failure, and lift each other up personally and professionally. Woven throughout the book are lessons and stories from accomplished women like Susan Lyne, Randi Zuckerberg, Mika Brzezinski, and Anne-Marie Slaughter, who have faced road blocks and overcome them by forging new paths, being unapologetically ambitious, and never taking no for an answer. Readers are also offered a glimpse into Saujani?s personal story, including her immigrant upbringing and the insights she gleaned from running a spirited campaign for U.S. Congress in 2010. Above all else, Women Who Don?t Wait In Line is an inspiring call from a woman who is still deep in the trenches. Saujani aims to ignite her fellow women--and enlist them in remaking America
Keywords: Women in the professions